Managers' viewpoint on factors influencing their commitment to safety: An empirical investigation in five Finnish industrial organisations. (July 2017) - Tappura, S.; Nenonen, N.; Kivistö-Rahnasto, J.
Highlights: Managers' strong commitment to safety is critical to success in safety management. We examine the organisational factors influencing managers' commitment to safety. Role overload, production demands and negative attitudes hinder managers' commitment. Increasing safety awareness and organisational support promote managers' commitment. We suggest organisational measures to support managers' commitment to safety. Abstract: Managers' strong commitment to safety is a key element of a successful safety management, culture and climate. Several studies have approached managers' commitment from the employees' point of view, but research approaching commitment from the managers' viewpoint is scarce. This qualitative study aims to identify the organisational factors that hinder or promote managers' commitment to safety and to suggest organisational measures that can be applied to support managers' commitment to safety. A total of 49 managers in five industrial organisations were interviewed. In addition, a workshop for the safety professionals of the participating companies was organised to review the interview results and to suggest organisational measures to support managers' commitment to safety. The managers identified role overload, production demands, overly formal safety procedures, external safety goals, workforce attitudes and managers' attitudes as the most common factors hindering their commitment to safety. On the other hand, the factors that promote managers' commitment to safety are increasing managers' safety awareness, influencing managers' safety attitudes, recognising managers' safety commitment, emphasising managers' safety responsibilities, developing adequate organisational safety procedures, superiors' encouragement and support, benchmarking others' safety activities, understanding the economic effects of safety, and safety improvement. The suggested organisational measures to support managers' commitment to safety include inspirational and participative management training; appropriate safety objectives; peer, superior and top management support; campaigns and competitions; employee safety training; and simplified safety procedures and reporting. The study expands on previous studies on supervisors' safety engagement and suggests practical organisational measures to promote managers' commitment to safety.